2001
DOI: 10.1074/jbc.m009134200
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor PTEN Is Phosphorylated by the Protein Kinase CK2 at Its C Terminus

Abstract: The tumor suppressor phosphatase PTEN regulates cell migration, growth, and survival by dephosphorylating phosphatidylinositol second messengers and signaling phosphoproteins. PTEN possesses a C-terminal noncatalytic regulatory domain that contains multiple putative phosphorylation sites, which could play an important role in the control of its biological activity. The protein kinase CK2 phosphorylated, in a constitutive manner, a cluster of Ser/Thr residues located at the PTEN C terminus. PTEN-phosphorylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
569
1
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 582 publications
(618 citation statements)
references
References 46 publications
30
569
1
9
Order By: Relevance
“…PTEN can be ubiquitinated and degradaded by several ubiquitin E3 ligases, such as NEDD4 and the X-linked inhibitor of apoptosis protein Wang et al, 2007;Van Themsche et al, 2009). Phosphorylation of PTEN by casein kinase 2 or GSK3b also controls PTEN stability by promoting ubiquitination (Torres and Pulido, 2001;Al-Khouri et al, 2005). Unlike casein kinase 2 and GSK3b, ROCK1-mediated PTEN phosphorylation at S380 upregulates the stablilty of PTEN (Vemula et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN can be ubiquitinated and degradaded by several ubiquitin E3 ligases, such as NEDD4 and the X-linked inhibitor of apoptosis protein Wang et al, 2007;Van Themsche et al, 2009). Phosphorylation of PTEN by casein kinase 2 or GSK3b also controls PTEN stability by promoting ubiquitination (Torres and Pulido, 2001;Al-Khouri et al, 2005). Unlike casein kinase 2 and GSK3b, ROCK1-mediated PTEN phosphorylation at S380 upregulates the stablilty of PTEN (Vemula et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…La protéine PTEN est phosphorylée par CK2 sur son extrémité régu-latrice carboxy-terminale. Cette phosphorylation règle négativement l'activité de la phosphatase en bloquant son intégration dans un complexe macromoléculaire nécessaire pour son adressage à la membrane plasmique [34]. En neutralisant PTEN, la CK2 potentialise l'action essentielle de la PI3K et de la PKB (protéine kinase B) pour assurer la survie cellulaire.…”
Section: Ck2βunclassified
“…Le produit du gène suppresseur de tumeur PTEN antagonise l'action anti-apoptotique de la PI3K [33]. La phosphorylation de PTEN par CK2 entraîne une inhibition de son activité phosphatase [34]. TNFα: tumor necrosis factor α; FRZ: récep-teur frizzled; Dsh: dishevelled; GSK3β: glycogen synthase kinase 3β; Fas L: Fas ligand; Fas R: récépteur de Fas L; PI3K: phosphatidylinositol 3-kinase; Cyt C: cytochrome C; PKB: protéine kinase B, IKK: IκB-kinase.…”
Section: Ck2βunclassified
“…A cluster of phosphorylation sites (S370, S380, T382, T383 and S385) on its conserved but structurally flexible C-terminal regions was mapped, and casein kinase 2 was shown to be able to phosphorylate these sites (Vazquez et al, 2000;Torres and Pulido, 2001). On the basis of these studies and the crystal structure of PTEN (Lee et al, 1999), an attractive model has been raised: phosphorylation of these sites keeps PTEN in the cytoplasm and thus inactive (in terms of its lipid phosphatase activity); but after dephosphorylation, the C2 domain of PTEN is probably more exposed allowing translocation of PTEN to the plasma membrane to antagonize PI3K-Akt signaling.…”
Section: Two General Mechanisms For Pten Post-translational Regulationmentioning
confidence: 99%
“…For example, as mentioned above, PTEN phosphorylation (Vazquez et al, 2000;Torres and Pulido, 2001;Maccario et al, 2007) and its multiple associating proteins (Tolkacheva et al, 2001;Okahara et al, 2004) have been suggested to regulate its protein stability, presumably via ubiquitin-mediated proteasomal degradation. In addition, deregulation of PTEN protein stability control might be involved in cancer development, as we discussed earlier.…”
Section: Regulation Of Pten By Ubiquitinationmentioning
confidence: 99%